The Skeptic's Guide to the Genealogy - Holvey, Benjamin (Stance: an international undergraduate philosophy journal, 2019)
This paper seeks to evaluate Nietzsche’s positive ethical vision through a focus on the plausibility of his moral-historical account as it appears in On the Genealogy of Morals. It is then argued that Nietzsche’s account of the “slave revolt in morality” contains shortcomings that necessitate further inquiry into Nietzsche’s consequent ethical vision. Furthermore, the paper goes on to demonstrate that if a proper historical context for the “slave revolt in morality” cannot be identified, or if it cannot be shown that Nietzsche’s ethical vision can stand without such a context, then a neo-Nietzschean ethic must be set aside.